A Simple and Direct Method for the Palladium‐Catalyzed Oxidative Coupling of Unactivated Allylarenes with Classic Arenes. Issue 6 (9th May 2014) - Jin, Weiwei; Wong, Wing‐Tak; Law, Ga‐Lai
Abstract An efficient route to engineer vinylarene structures by the PdII‐catalyzed oxidative coupling of unactivated allylarenes with classic arenes was developed. The methodology features the use of unactivated allylarenes with no prefunctionalization and classic arenes without installed directing groups. A variety of vinylarenes and their saturated derivatives were obtained.